STRATEGI MEMBANGUN KEPATUHAN SUKARELA UMKM DITINJAU DARI ASPEK PERSEPSI KEADILAN PAJAK DAN KEPERCAYAAN PADA OTORITAS : Systematic Literature Review - Laelatun Mazaya Maya (Perwira Journal of Economics & Business, 2026)
This study examines the strategies of fostering voluntary tax compliance among MSMEs from the perspectives of perceived tax fairness and trust in tax authorities.  Voluntary tax compliance by MSMEs is a crucial factor in strengthening the national revenue base within the framework of an equitable and sustainable tax system.  However, the level of MSMEs tax compliance in Indonesia remains relatively low. One factor is perceptions of tax fairness and their level of trust in tax authorities. This literature based on study adopts a qualitative approach using a Systematic Literature Review (SLR) of relevant academic articles obtained through Google Scholar.  The SLR process was conducted through four stages : identification, screening, eligibility and included.  Based on the selection process, 12 scientific articles met the inclusion criteria and were included in the review. The findings indicate that perceptions of tax fairness, particularly distributive and procedural fairness, have a positive effect on voluntary tax compliance among MSMEs.  Trust in tax authorities also exerts a positive influence on voluntary compliance.  Moreover, several studies reviewed position trust not only as an independent variable with a direct effect, but also as a mediating variable that strengthens the relationship between perceived tax fairness and voluntary tax compliance among MSMEs.  Therefore, it can be concluded that voluntary tax compliance among MSMEs is influenced not only by regulatory and economic factors, but also by psychological and institutional relationships between taxpayers and tax authorities.  Practically, these findings provide policy implications for tax authorities to design strategies for improving MSME compliance by emphasizing fairness, transparency, and the strengthening of institutional relationships in order to promote long-term voluntary tax compliance.